Politics and Media Hegemony Policy in Indonesia - Erman Anom; Hamdani M. Syam; Nur Anisah; Dafrizal Samsudin (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
This research aims to help those trying to master the media and political power in Indonesia and use the media as a tool to build community system from the Dutch colonial rule to the independence era, particularly from 1999 to 2019. This study is about how the system formed the media under the political policy until it developed into Â Â a base media in Indonesia between the era of the Dutch conquest and the year 2019. To achieve the objective of the study, investigation has been made upon media as a factor that affects the formation of the base to control the freedom of the media by using the investigation approach on history through document analysis and deep interview. The finding shows that forming a base that controls the freedom of the media is based on a proses which is designed soberly to fit with the philosophy and the value which is practiced by the ruling leader, and became the base of the national media activist in Indonesia.